E-learning e as redes sociais - Alves, Bruno (2011)
The e-learning platforms or Learning Management Systems are an actual reality that’s emerging in the world of education and in the actual context of Information Society. This investigation essay has, as principal goals to understand the relation between those and the social network phenomena. For that, it was created a query to users from both contexts and to establish a bridge between their functionalities and activities fulfilled in the existing social networks. This essay also shows some future perspectives in the education field and the integration of new technologies in those areas as aggregation and development tools of the teaching processes, as well the need of reevaluate the fundamental aspects of education, from curricula to the creation of individual learning goals.